Physical and Mechanical Properties of Bamboo Oriented Strand Board Prepared from Alkali-Immersed Strands - Sena Maulana; Tarmizi Taher; Aditya Rianjanu; Melany Febrina; Sarah Agustina; Rio Ardiansyah Murda; Wahyu Hidayat; Yazid Bindar (Science and Technology Indonesia, 2023)
In this work, the physical and mechanical properties of bamboo oriented strand board (BOSB) prepared from alkali-immersed strands were examined. The Dendrocalamus asper strands were modified with alkali treatment by immersing them in 1% sodium hydroxide solution for 1, 2, and 3 hours. Three-layers BOSBs (30 x 30 x 0.9 cm3) were prepared using phenol-formaldehyde (PF) adhesive of 8% concentration and 1% paraffin. According to JIS A 5908:2003 Standard, the physical and mechanical characteristics of BOSB were evaluated (JSA, 2003). The study showed that alkali treatment improved the dimensional stability of BOSB. Immersion in 1% sodium hydroxide solutions enhanced internal bonding (IB). The longer the immersion time, the better the WA, TS, and IB values. However, alkali treatment decreased the bending strength, i.e., modulus of elasticity (MOE) and modulus of rupture (MOR). The physical and mechanical properties of all BOSBs met the commercial standard, except the BOSBs prepared from strand with alkali immersion treatment by 1% sodium hydroxide solution for 3 hours. Alkali immersion treatment of D. asper strands for producing BOSB for 1-2 hours was still acceptable. The results could provide an alternative method to produce high-performance oriented strand board using bamboo as the raw materials.